Los valores y la convivencia una tarea significativa en la vida escolar (2017)
In the San Jerónimo Emiliani school, Santana branch, was developed a project about school environment and  values in  students of  third grade. The main objective of  this paper is  to describe the importance of educational and leisure activities on a healthy school environment and the rescue of good habits; at the same time, to reflect about the importance to work in the educational projects focused on a culture of peace and healthy living.